Synthesis and anti-SARS-CoV-2 activity of deuterated GS-441524 analogs. (17th August 2022) - Zheng, Wei; Hu, Tianwen; Zhang, Yumin; Wei, Daibao; Xie, Yuanchao; Shen, Jingshan
Graphical abstract: Abstract: The COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is continuing to spread around the world. GS-441524 is the parent nucleoside of remdesivir which is the first drug approved for the treatment of COVID-19, and demonstrates strong activity against SARS-Cov-2 in vitro and in vivo. Herein, we reported the synthesis of a series of deuterated GS-441524 analogs, which had deuterium atoms up to five at the ribose and the nucleobase moieties. Compared to GS-441524, all the deuterated compounds showed similar inhibitory activities against SARS-CoV-2 in vitro.